Just in time: how evidence-on-demand services support decision making in Ontario's child and youth mental health sector. (25th January 2016) - Notarianni, Maryann; Sundar, Purnima; Carter, Charles
Abstract : Using the best available evidence to inform decision making is important for the design or delivery of effective health-related services and broader public policy. Several studies identify barriers and facilitators to evidence-informed decision making in Canadian health settings. This paper describes how the Ontario Centre of Excellence for Child and Youth Mental Health, as an intermediary organisation, facilitates evidence-informed decision making at organisational and system levels in Ontario's child and youth mental health sector through two unique knowledge mobilisation services. This paper describes these services, offering them as exemplars for other sectors seeking to support evidence use in policy and practice decision making.